Semantic content of social lexicon in Uzbek and English languages - Anvarova , Sayyorakxon (The Lingua Spectrum, 2025)
This article explores the semantic content of social lexicon in Uzbek and English languages. Social lexicon includes words and expressions that describe social relationships, roles, institutions, and behavioral norms in society. The study analyzes how cultural, historical, and social factors influence the development and usage of social vocabulary in both languages. Particular attention is given to words that express status, politeness, authority, and social hierarchy. Comparative analysis highlights the similarities and differences in conceptualizing social realities in Uzbek and English cultures. By examining specific lexical items and their semantic fields, the article aims to reveal how language reflects and shapes social cognition. The research is based on linguistic and sociolinguistic sources, as well as examples from modern usage. This study is useful for linguists, sociologists, and language learners interested in cross-cultural communication and translation studies.